2018
DOI: 10.3390/genes9060296
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Knock-in of a Point Mutation in Porcine Fibroblasts Using the CRISPR/Cas9-GMNN Fusion Gene

Abstract: During CRISPR/Cas9 mediated genome editing, site-specific double strand breaks are introduced and repaired either unspecific by non-homologous end joining (NHEJ) or sequence dependent by homology directed repair (HDR). Whereas NHEJ-based generation of gene knock-out is widely performed, the HDR-based knock-in of specific mutations remains a bottleneck. Especially in primary cell lines that are essential for the generation of cell culture and animal models of inherited human diseases, knock-in efficacy is insuf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 35 publications
0
22
0
1
Order By: Relevance
“…While SCR7 was shown to increase HDR mediated integration of dsDNA into fetal porcine fibroblasts [55], the efficiency to introduce a point mutation by ssODN could not be increased [56]. Estimation of NHEJ and HDR by an extrachromosomal fluorescent reporter construct in H1 cells did not show a significant difference in HDR or NHEJ efficiency between SCR7 treated and non-treated controls [57].…”
Section: Dna Ligase IVmentioning
confidence: 82%
“…While SCR7 was shown to increase HDR mediated integration of dsDNA into fetal porcine fibroblasts [55], the efficiency to introduce a point mutation by ssODN could not be increased [56]. Estimation of NHEJ and HDR by an extrachromosomal fluorescent reporter construct in H1 cells did not show a significant difference in HDR or NHEJ efficiency between SCR7 treated and non-treated controls [57].…”
Section: Dna Ligase IVmentioning
confidence: 82%
“…Mechanistically, SCR7 blocks the NHEJ pathway by binding to DNA ligase IV, a key enzyme of the NHEJ pathway, in a concentration-dependent manner (Vartak and Raghavan, 2015). Specifically, it works by reducing the affinity of DNA ligase IV for DSBs (Gerlach et al, 2018). SCR7 binds to the DNA-binding domain of DNA ligase IV, thereby preventing DNA ligase IV from binding to the DNA ends, resulting in the elimination of the NHEJ pathway (Vartak and Raghavan, 2015).…”
Section: Methods For Enhancing Clustered Regularly Interspaced Short mentioning
confidence: 99%
“…Interestingly, experiments have shown that the addition of SCR7 does not improve HDR efficiency during genome editing. In contrast, coordinated expression of Cas9 in the HDR-dominant cell cycle is more efficient in inducing HDR than inhibition of NHEJ (Gerlach et al, 2018). Nonetheless, existing studies have shown that these manipulations may be difficult to perform, or the process of manipulation may cause greater damage to cells.…”
Section: Methods For Enhancing Clustered Regularly Interspaced Short mentioning
confidence: 99%
“…This engineered Cas9-geminin construct increased the HDR rate by 1.87-fold compared with wild-type Cas9 in HEK-293T cells [88]. The efficacy of the hCas9-geminin approach was subsequently confirmed in human pluripotent stem cells and porcine fibroblasts [120,121], making it the most promising tool for enhancing HDR ( Figure 6). Lomova et al, found that there was an additive effect between manipulation of Cas9 expression and cell cycle synchronization via RO-3306, which improved the HDR/NHEJ ratio by an average of 20-fold compared with the control condition in hPSCs [118].…”
Section: Cas9 Activity Paired With the Hdr-active Cell Cycle Phasementioning
confidence: 95%